Scarcity in the Modern World History, Politics, Society and Sustainability, 1800-2075 - Jonsson, Fredrik Albritton; Brewer, John; Fromer, Neil; Trentmann, Frank (Bloomsbury Academic, 2019)
Scarcity in the Modern World brings together world-renowned scholars to examine how concerns about the scarcity of environmental resources such as water, food, energy and materials have developed, and subsequently been managed, from the 18th to the 21st century. These multi-disciplinary contributions situate contemporary concerns about scarcity within their longer history, and address recent forecasts and debates surrounding the future scarcity of fossil fuels, renewable energy and water up to 2075. This book offers a fresh way of tackling the current challenge of meeting global needs in an increasingly resource-stressed environment. By bringing together scholars from a variety of academic disciplines, this volume provides an innovative multi-disciplinary perspective that corrects previous scholarship which has discussed scientific and cultural issues separately. In doing so, it recognizes that this challenge is complex and cannot be addressed by a single discipline, but requires a concerted effort to think about its political and social, as well as technical and economic dimensions. This volume is essential for all students and scholars of environmental and economic history.